Kontrak Kerja Sebagai Kerangka Dasar Dan Perlindungan Hukum Ditinjau Berdasarkan Hukum Perdata - Novianti, Erlina; Taun, Taun (Peneliti.net, 2023)
Business contracts are the basic framework used by economic actors, especially in the world of trade, namely to maintain relations between business actors, as well as a form of business dispute resolution. Therefore, in making agreements and resolving disputes, it must be based on legal provisions regulated in book III of the Civil Code. The purpose of writing this scientific article is to find out the role of contracts so that they can be used as a basic framework and legal protection in business activities. The research method used in this study is normative juridical and uses a statutory and historical approach. In writing this article, it is explained that data analysis is data modeling with the aim of finding useful information, informing conclusions and supporting decision making. The results of this study are contract law protection which is based on the principle of pacta sunt servanda. In a cooperation agreement, a business contract is needed, namely to ensure that the agreed agreement can run smoothly.